2016
DOI: 10.1016/j.bbmt.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes of 8/8 and 7/8 Allele–Matched Unrelated Bone Marrow Transplantation and Single-Unit Cord Blood Transplantation in Adults with Acute Leukemia

Abstract: To investigate an up-to-date alternative donor selection strategy, we compared the transplantation outcomes of 8/8 and 7/8 allele-matched unrelated bone marrow transplantation (UBMT) with those of umbilical cord blood transplantation (UCBT) and redefined the role of UCBT with extended analysis. Using Cox and competing risk regression analyses, we analyzed the transplantation outcomes in adult patients with acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML). A total of 2472 first myeloablative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 32 publications
(54 reference statements)
3
60
0
Order By: Relevance
“…Similar to previous reports (Burnett et al , ; Michelis et al , , ), our data also demonstrated that donor source did not affect transplant outcomes in CR2, except that unrelated cord blood transplantation (UCBT) gave a higher TRM in the univariate analysis. However, several studies have demonstrated highly similar survival results between UCBT and UBMT in adult AML (Terakura et al , ). In addition, our data demonstrated that the intensity of the conditioning regimen did not affect survival, relapse and TRM in CR2, which is consistent with previous studies (Burnett et al , ; Michelis et al , , , ).…”
Section: Multivariate Analysis Of the Overall Mortality Treatment Famentioning
confidence: 93%
“…Similar to previous reports (Burnett et al , ; Michelis et al , , ), our data also demonstrated that donor source did not affect transplant outcomes in CR2, except that unrelated cord blood transplantation (UCBT) gave a higher TRM in the univariate analysis. However, several studies have demonstrated highly similar survival results between UCBT and UBMT in adult AML (Terakura et al , ). In addition, our data demonstrated that the intensity of the conditioning regimen did not affect survival, relapse and TRM in CR2, which is consistent with previous studies (Burnett et al , ; Michelis et al , , , ).…”
Section: Multivariate Analysis Of the Overall Mortality Treatment Famentioning
confidence: 93%
“…Others observed similar rates of severe acute GvHD after CBT and 8/8 matched BMT but higher rates after 7/8 matched BM grafting while the incidence of extensive chronic GvHD was significantly lower after CBT compared with 8/8 and 7/8 BM grafting (178). …”
Section: Stem Cell Sourcesmentioning
confidence: 95%
“…More recent studies support these results (143, 177), respectively. Terakura and colleagues analyzing HSCT outcomes in patients with ALL and AML reported similar OS and NRM comparing 8/8 allele-matched unrelated BMT with CBT leading to the conclusion that CB could be a preferable alternative (178). …”
Section: Stem Cell Sourcesmentioning
confidence: 99%
“…16 This analysis included 2472 myeloablative transplants (1001 HLA 8/8; 656 HLA 7/8; 815 cord blood transplants). Overall, recipients of HLA 7/8 matched unrelated donor transplantation had lower overall survival, higher GVHD and higher non-relapse mortality compared to HLA 8/8 matched unrelated and cord blood transplant recipients.…”
Section: Basic Principles Of Hla Mismatchingmentioning
confidence: 99%